KEKUATAN HUKUM ACTA VAN DADING SEBAGAI HASIL KESEPAKATAN MEDIASI DALAM GUGATAN PERDATA - Triana Dewi Seroja; Ampuan Situmeang; Febri Jaya; Supardi (Fakultas Hukum Universitas Kristen Indonesia, 2020)
Mediation has been regulated in Paragraph 1 Article 1 PERMA no. 1 2016, which is related to the practice of judicial mediation.